2015
DOI: 10.1093/ijnp/pyu097
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Neurochemical Changes in Mesostriatal Dopaminergic Regions of the Rat after Chronic Administration of the Cannabinoid Receptor Agonist WIN55,212-2

Abstract: Background:The endocannabinoid system interacts extensively with other neurotransmitter systems and has been implicated in a variety of functions, including regulation of basal ganglia circuits and motor behavior. The present study examined the effects of repeated administration of the nonselective cannabinoid receptor 1 agonist WIN55,212-2 on locomotor activity and on binding and mRNA levels of dopamine receptors and transporters and GABAA receptors in mesostriatal dopaminergic regions of the rat.Methods:Rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 116 publications
0
10
0
3
Order By: Relevance
“…Further studies have consistently repeated these results and have demonstrated that an acute administration of either Δ9‐THC, WIN55,212‐2, HU‐210 and CP55,940 results in a receptor‐specific activation of the ventral tegmental area and substantia nigra dopamine neurons in vivo and in vitro (Gessa et al ., ; Wu & French, ; Cheer et al ., ; Morera‐Herreras et al ., ; Ginovart et al ., ; Fanarioti et al ., ; Perdikaris et al ., ). These results have demonstrated that CB 1 agonists may act as dopamine agonist‐like in the meso‐cortical dopamine circuitry, known to be involved in the brain's reward mechanism (Chen et al ., ; Tanda et al ., ).…”
Section: Cannabinoids and The Dopaminergic Systemmentioning
confidence: 97%
See 1 more Smart Citation
“…Further studies have consistently repeated these results and have demonstrated that an acute administration of either Δ9‐THC, WIN55,212‐2, HU‐210 and CP55,940 results in a receptor‐specific activation of the ventral tegmental area and substantia nigra dopamine neurons in vivo and in vitro (Gessa et al ., ; Wu & French, ; Cheer et al ., ; Morera‐Herreras et al ., ; Ginovart et al ., ; Fanarioti et al ., ; Perdikaris et al ., ). These results have demonstrated that CB 1 agonists may act as dopamine agonist‐like in the meso‐cortical dopamine circuitry, known to be involved in the brain's reward mechanism (Chen et al ., ; Tanda et al ., ).…”
Section: Cannabinoids and The Dopaminergic Systemmentioning
confidence: 97%
“…Accordingly, an administration of Δ9‐THC for 21 days has down‐regulated tyrosine hydroxylase mRNA expression in the substantia nigra and in the ventral tegmental area midbrain nuclei, but not in the cortex or striatum (Ginovart et al ., ). Further studies have replicated this result (Fanarioti et al ., ; Perdikaris et al ., ), and they have added that alterations to tyrosine hydroxylase expression was observed up to 7 days following cessation (Perdikaris et al ., ). Altogether, these studies show that following chronic treatment with CB 1 agonists there are some alterations in the activity of the dopaminergic‐neurons.…”
Section: Cannabinoids and The Dopaminergic Systemmentioning
confidence: 99%
“…The absence of tolerance is quite remarkable since it is generally assumed that CB 1 receptors are prone to plasticity [13,16,36,40]. However, it has been previously reported that repeated administration of WIN55,212-2 does not lead to behavioral tolerance despite producing acute and sustained motor-suppressant effects [41]. Whereas chronic treatment with WIN results in slight CB 1 receptor desensitization in mice, it was much lower than when treated with Δ 9 -THC [65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, evidence from rats with pentylenetetrazole (PTZ)-induced tonic-clonic seizures shows that chronic exposure to cannabinoids did not affect seizure susceptibility [67]. Therefore, the development of tolerance to CB 1 agonists seems to be dependent on several factors, including the used compound, experimental protocol, and dose [41,68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation